Perspektif Maslahah Mursalah Terhadap Surat Pernyataan Suami Tidak Merujuk Bekas Isteri Di Masa Iddah: (Studi Kasus di KUA Kecamatan Ploso Kabupaten Jombang) - Misbachul Fitri, Abdul Basit; Sajidin, Muhammad Yulis (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Maslahah is everything that is beneficial for humans and rejects harm or damage. The misconduct here involves the prospective groom conducting a covert marriage that could harm the former wife. The researcher attempts to explain the policy argument of the Religious Affairs Office (KUA) of Ploso District regarding the statement letter of not reconciling with the ex-wife during the iddah period and the maslahah review of the husband's statement letter of not reconciling with the ex-wife during the iddah period. The type of research is field research. (penelitian Lapangan). The data used are cases in society. Data collection technique through interviews based on primary data, namely brides-to-be, their families, PPN, and PPN assistants at the KUA Ploso sub-district, Jombang district, supported by secondary data from books related to this research. The approach in this research uses a normative approach analyzed through descriptive analysis. The research results explain that the argumentation of the KUA (Office of Religious Affairs) in Ploso District, Jombang Regency, in issuing a policy letter to prohibit remarrying an ex-wife during the iddah period is a form of caution in conducting marriages to prevent any misconduct or legal violations by the male groom who is a widower. Review of maslahah mursalah regarding the policy letter to not reconcile with the ex-wife while still in the iddah period to prevent or avoid, such as rejecting harm or damage.